From archives to archival science Elements for a discursive construction - Barros, Thiago Henrique Bragato [UNESP]; De Moraes, Joáo Batista Ernesto [UNESP] (My University, 2010)
This work tries to outline the theoretical background established by archival science manuals, based mainly on discourse analysis as a key discipline to understand which the differences are and points of conceptual commonality in archival science traditions studied that to some extent, are additional. As archival science is a product of historically constructed knowledge, the context of conceptual production ultimately reflects in the different schools of thought and in the methodological approach. The manuals discussed here were selected by their canon and their wide dissemination in the archival science field, and are: the Manual for the arrangement and description of archives of the Association of Dutch Archivists (1898), and Jenkinson's A manual of archive administration including the problems of war archives and archive making. We considered how in these manuals two key concepts are discussed as for organization methodology in archival science: description and classification, establishing, from these concepts, which are the intertwined discourses in these texts and relating them to their historical aspects.